Analysis of User Experience on SPOTA UNTAN Using Heuristic Walkthrough Method - Caroline Caroline; Helen Sastypratiwi; Haried Novriando (Journal of Information System and Informatics, 2023)
SPOTA UNTAN is an abbreviation for Sistem Pendukung Outline Tugas Akhir for the Informatics study program at Tanjungpura University. SPOTA UNTAN was developed within the Informatics study program at Tanjungpura University in 2008. SPOTA UNTAN is an information system that support students in submitting their final project topics. As for now, SPOTA UNTAN has undergone several updates, including the new features to enhance the information system functionality. As its interface has undergone some changes, such as the addition of content, however, the CSS framework (colors, fonts, shapes, etc.) still retains the original design and not yet updated to align with the user experience. Therefore, several analyses are needed to address these uncertainties from a user interface perspective by usability tests. The study will apply the Heuristic Walkthrough method, which combines Cognitive Walkthrough and Heuristic Evaluation. The analysis will involve 5 expert evaluators in UI/UX. This study result showed a total of 39 recommendations for problem resolution, categorized into functional feature improvements and interface enhancements.